The Restrictive IV Fluid Trial in Severe Sepsis and Septic Shock (RIFTS): A Randomized Pilot Study*. Issue 7 (July 2019) - Corl, Keith A.; Prodromou, Michael; Merchant, Roland C.; Gareen, Ilana; Marks, Sarah; Banerjee, Debasree; Amass, Timothy; Abbasi, Adeel; Delcompare, Cesar; Palmisciano, Amy; Aliotta, Jason; Jay, Gregory; et al.
Abstract : Objectives: It is unclear if a low- or high-volume IV fluid resuscitation strategy is better for patients with severe sepsis and septic shock. Design: Prospective randomized controlled trial. Setting: Two adult acute care hospitals within a single academic system. Patients: Patients with severe sepsis and septic shock admitted from the emergency department to the ICU from November 2016 to February 2018. Interventions: Patients were randomly assigned to a restrictive IV fluid resuscitation strategy (⩽ 60 mL/kg of IV fluid) or usual care for the first 72 hours of care. Measurements and Main Results: We enrolled 109 patients, of whom 55 were assigned to the restrictive resuscitation group and 54 to the usual care group. The restrictive group received significantly less resuscitative IV fluid than the usual care group (47.1 vs 61.1 mL/kg; p = 0.01) over 72 hours. By 30 days, there were 12 deaths (21.8%) in the restrictive group and 12 deaths (22.2%) in the usual care group (odds ratio, 1.02; 95% CI, 0.41–2.53). There were no differences between groups in the rate of new organ failure, hospital or ICU length of stay, or serious adverse events. Conclusions: This pilot study demonstrates that a restrictive resuscitation strategy can successfully reduce the amount of IV fluid administered to patients with severe sepsis and septic shock compared with usual care. Although limited by the sample size, we observed no increase in mortality, organ failure, or adverse events. These findings further support that a restrictive IV fluid strategy should be explored in a larger multicenter trial. Abstract : Supplemental Digital Content is available in the text.